Numerical modelling of hydrogen leakages in confined spaces for domestic applications - Thawani, Bonny; Hazael, Rachael; Critchley, Richard (Elsevier, 2024)
The UK government tentatively plans to use hydrogen for domestic applications by 2035. While the use of hydrogen aims to reduce the dependence on hydrocarbons, certain factors need consideration. Since hydrogen is much lighter, and more reactive than methane, it is crucial to understand the change in risk for accident scenarios involving hydrogen in a domestic setting. Numerical modelling was used to simulate the leakage of hydrogen and methane in small, enclosed spaces such as kitchen cupboards. The k- ε turbulence model was used along with the species transport model to simulate the leakage of gas for different inlet locations and leak diameters (1.8 mm–7.2 mm). From the modelling study, it was observed that hydrogen and methane both tend to stratify from top of the control volume to the bottom. The key finding was that, under adverse conditions (leak from a 7.2 mm diameter hole) and due to greater volumetric flow, hydrogen tends to reach equilibrium concentration 45s faster than methane for a total leak duration of 600s. Additionally, it was noted that cases with leak inlet locations near corners had 28% lower hydrogen concentrations, and 25% lower methane concentrations as compared to leak inlet locations near the centre of the cupboard.
This paper was also presented at: DSDS24, Cranfield Defence and Security Doctoral Symposia 2024, 13-14 November 2024, STEAM Museum, Swindon, UK
Keywords: Hydrogen; Energy; Security; Modelling and simulation; Gas leak